Pengukuran Kecepatan Suara dalam Media Air Menggunakan Sensor Ultrasonik - Miftakhul Khanan; Ahmad Ashari (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2020)
The speed of sound in water varies depending on the condition. There are several factors that affect the difference in the speed of sound in water, such as the viscosity, temperature, pressure, etc. In this study, designed a tool to measure the speed of sound in water by utilizing ultrasonic waves.The ultrasonic sensor used consists of transmitter and receiver. The method used is indirect method by using sound reflection. The 40kHz ultrasonic wave used on the transmitter is generated by the AD9850 signal generator. Signals received receiver in and processed on a microcontroller through an LM393 comparator that makes the signal HIGH and LOW so it can be read directly on the digital pins of microcontroller.Measurements were made at a water temperature of 27oC with 1 meter test medium. The measurement is done on variation of distance from 5-90 cm with span of 5 cm. By knowing the time difference between the transmitted and received signal and the known wave range, the speed of sound in the water obtained in the study was (1394 ± 27) m / s with the determination coefficient of 0.998.